Origin, biochemical composition and vertical flux of particulate organic matter under the pack ice in Terra Nova Bay (Ross Sea, Antarctica) during late summer 1995 - PUSCEDDU, ANTONIO; CATTANEO VIETTI R; ALBERTELLI G; FABIANO M. (Polar Biology, 1999)
Water samples and particulate materials settling under the pack ice were collected in an ice-covered area near the Terra Nova Bay Italian Station during late summer 1995, in order to study short-term changes in the biochemical composition of particulate organic matter. At the end of the study period the phytoplankton biomass increase (up to >3.0 μg chlorophyll-a 1-1) was probably related to the intrusion under the pack ice I of chlorophylls-enriched surface waters coming from the near ice-free area. Such increase was associated also with a notable increase in particulate organic matter concentrations, as well as in particulate organic matter vertical fluxes (up to >100 mg C m-2 day-1). Proteins were the most abundant biochemical class of particulate organic matter (on average about 49%), followed by lipids (29%) and carbohydrates (22%). By contrast, organic matter collected in the sediment trap was characterized by the dominance of lipids (about 55% of the total biopolymeric carbon flux) over carbohydrates (28%) and proteins (17%). The hydrolizable particulate biopolymeric carbon accounted for about 23% of total biopolymeric carbon. This value was about one-half of that found in ice-free waters, suggesting that the suspended particulate organic material under the pack ice was less digestible than in ice-free waters or was already partially digested. Despite this, and the decay of labile organic compounds in the sediment trap during the deployment, material settling towards the sea bottom under the pack ice in Terra Nova Bay, owing to its high lipid content, might represent an important high-quality food source for benthic consumers. Finally, assuming as possible the intrusion under sea ice of primary organic matter-enriched waters, we hypothesize the occurrence of a 'fertilization' effect deriving from ice-melting areas towards under-ice waters, supplying the latter with an additional rate of primary organic matter.